Prevalence and determinants of periodontitis among a population with knee osteoarthritis, a cross-sectional study at the Douala General Hospital (Littoral, Cameroon) - Herna Stella Chimy Tchounchui; Fernando Kemta Lekpa; Sylvain Raoul Simeni Njonnou; Clarisse Mapa-Tassou; Christian Deube Ngako; Faustin Atemkeng Tsatedem; Félicité Soh Maleu Mbah; Lawrence Essama Eno Belinga; Francine Same Bebey; Jérôme Ateudjieu; Simeon Pierre Choukem (Scientific Reports)
Abstract Osteoarthritis (OA) is a slowly evolving, multifactorial disorder that affects joints, particularly the knee. Periodontitis is an infection of the tissues supporting the teeth, leading to significant tooth loss. Recent studies suggest an association between Knee OA (KOA) and periodontitis, with the prevalence of periodontitis increasing with the severity of KOA. We aimed to determine the prevalence and distribution of periodontitis and the association between the severity of KOA and periodontitis in subjects living with KOA. A cross-sectional study was conducted in an outpatient clinic at the Rheumatology unit of the Douala General Hospital between October 2022 and June 2023. Data were collected using a questionnaire, an endo-buccal examination grid, radiological images and medical records. A multivariate analysis using logistic regression was performed, including the relevant variables in the bivariate analysis. We included 253 participants (201 women) with a median age of 63 years [54–70]. The mean visual analog scale was 52.7 ± 27.9 mm. The mean Lequesne index was 12.25 ± 5.03. Kellgren and Lawrence (K&L) grade 2 was predominant (61.7%), as was tricompartimental KOA (85.4%). The brushing method was appropriate for 40.3% of the participants, while more than a quarter (26.7%) were brushing their teeth for more than 3 min. The oral hygiene was good for only the third (33.6%) of the population. The prevalence of periodontitis was 62.5% [56.1–68]. Periodontitis was significantly associated with radiological K&L grade 4 (OR 5.39 [1.27–28.98]; p = 0.03), poor oral hygiene (OR 34 [7.46–277.71]; p < 0.001), visits to the dentist [in case of problems] (OR 8.54 [3.09–28.58]; p < 0.001) and brushing time (OR 21.93 [5.66–123.24]; p < 0.001). Many participants in this study had poor brushing habits, and only a few had good oral hygiene. Periodontitis is common in patients with KOA, affecting almost 2 patients out of three at the Douala General Hospital in Cameroon and is associated with the severity of KOA, poor oral hygiene and poor oral hygiene habits.